2013
DOI: 10.4103/0253-7613.117766
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of Piper betle Linn. leaves reduces nociception via modulation of arachidonic acid pathway

Abstract: Objectives:The objective of this study was to evaluate the peripheral analgesic effect of Piper betle leaf extract (PBE) along with establishing its putative mechanism of action.Materials and Methods:Male Swiss albino mice after pre-treatment (1 h) with different doses of PBE were injected 0.8% (v/v) acetic acid i.p.; the onset and number of writhes were noted up to 15 min. To evaluate the mechanism of action, the murine peritoneal exudate was incubated with PBE for 1 h, followed by exposure to arachidonic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The addition of FA (Group IV) significantly decreased the hepatic generation of ROS as also did PB (Fig. 2a) in agreement with previous studies [10].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The addition of FA (Group IV) significantly decreased the hepatic generation of ROS as also did PB (Fig. 2a) in agreement with previous studies [10].…”
Section: Resultssupporting
confidence: 92%
“…Experimental models have validated its antimicrobial, gastroprotective, antidiabetic, and hepatoprotective properties [4][5][6][7]. Additionally, studies using the Piper betle leaf extract have demonstrated its antioxidant, anti-inflammatory, and analgesic activity [8][9][10].…”
Section: Introductionmentioning
confidence: 93%
“…Administration of the extract significantly ( p < 0.05) reduced carrageenan‐induced paw oedema and reduced the number of acetic acid‐induced writhing and formalin‐induced licks in a dose‐dependent manner 113 . De et al also observed a reduced writhing response through modulation of the arachidonic acid pathway in the acetic acid‐induced writhing test on Swiss Albino mice using ethanolic extract of leaves 114 . The analgesic effect of the betel leaf was evaluated using the heat conduction process and the hot plate method of the eddy in mice and rat models.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%